Incidence of osteoporotic femur fractures in old people living in Kemerovo - T A Raskina; Yulia Valeryevna Averkieva (Современная ревматология, 2013)
Objective: to study the incidence rate of osteoporotic proximal femoral fractures in old persons from Kemerovo after 6, 12, and 24 months. Subjects and methods. The incidence of femur fractures was analyzed in people of 50 years or older who had been followed up in the Kemerovo units from 1 January 2004 to 31 December 2008. Results. In the examined period, the incidence of femur fractures by referrals for both sexes was 277.75 per 100,000 population 50 years of age and older: 179.59 for males and 335.96 for females. Among the Kemerovo dwellers, the least prevalence of femur fractures was noted in the old age group in 2004: 26.77 and 49.17 per 100,000 for males and females, respectively (p<0.05). The highest incidence of fractures was recorded in 2005 and was 40.59 and 79.64 per 100,000 for males and females, respectively (p<0.05). Femur fractures were found to be more common in women aged 50—79 years than in males of the same age. There were statistically significant group differences for the age groups of 50—54, 55—59, 65—69, 70—74, and 75—79 years (p<0.05). Among the persons aged 80 years or older, femur fractures were more frequently seen in the males than in the females (p>0.05). Conclusion. In the old women living in Kemerovo, the incidence of osteoporotic femur fractures was higher than that in the men within all years of the follow-up. The largest number of fractures was in the age group of 75 years or older in both male and female populations.